(untitled) (Fiep Bulletin - online, 2015)
This research delineates itself on the pedagogical practices of teachers of Physical Education, seeking to characterize what pedagogical approaches influence their teaching actions, regarding the choice of themes for the classes, the criteria that influence the choices of content and material and teaching spaces used in the development of lessons. In this sense, this work aims through a field survey, identify and characterize the pedagogical approaches applied in the teaching of Physical Education professors of the Municipal Public school of Cascavel district. The universe of the in loco study was the Cascavel district. The participants for this study, belonging to the sample should be part of some preliminary criteria: Teacher be formed or in process of formation in the Bachelor’s Degree in Physical Education, effected professor in Physical Education from 6 to 9 classrooms. The instrument for data collection was a questionnaire with open questions. Perceive the pursuit of physical education teachers by a reframing of their practice within the school where the student ceases to be only a body and becomes subject, showing the possibilities of critical and reflective action. The bias of health, yet found, is posited as an integral element of being and not as the only possible element assumes a context of integration with sociocultural elements showing that health is not only a matter of performance, but rather an action reflective about what we can do with these results. Such practices are a result of paradigm shifts within the Physical Education where we can say that the starting point is the teacher’s pedagogic practice and its commitment to providing a meaning in the teaching learning process.